2020
DOI: 10.34172/npj.2021.05
|View full text |Cite
|
Sign up to set email alerts
|

An overview of complications associated with deferoxamine therapy in thalassemia

Abstract: Thalassemic syndromes are the most common genetic diseases in the world that are related to blood transfusion and iron overload in the body. In ß-thalassemia major multiple blood transfusions due to ineffective erythropoiesis lead to iron excess in the body. Iron chelating agent deferoxamine is used to treat chronic iron overload in patients with β-thalassemia in an attempt to reduce morbidity and mortality related to deposition of excess iron in body tissue. However, a very short half-time, the need of repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…These differences were caused by the fact that splenectomized patients tend to be more prone to clinical complications [59]. Patients treated with DFO, which has a very short half-life that requires repetitive injections and non-targeted distribution in tissues, can develop brain, lung, and kidney damage that can cause other problems, such as peripheral neuropathy and glandular and growth disorders [60]; this requires more frequent physician consultations than other ICTs. The regression analysis related to consultations revealed that DFO, combined treatment, and a history of splenectomy were associated with an expected increase in the number of consultation services.…”
Section: Discussionmentioning
confidence: 99%
“…These differences were caused by the fact that splenectomized patients tend to be more prone to clinical complications [59]. Patients treated with DFO, which has a very short half-life that requires repetitive injections and non-targeted distribution in tissues, can develop brain, lung, and kidney damage that can cause other problems, such as peripheral neuropathy and glandular and growth disorders [60]; this requires more frequent physician consultations than other ICTs. The regression analysis related to consultations revealed that DFO, combined treatment, and a history of splenectomy were associated with an expected increase in the number of consultation services.…”
Section: Discussionmentioning
confidence: 99%
“…DFO treatment improves post-stroke cognitive dysfunction and long-term sensorimotor via a decrease in markers of oxidative stress, ferroptosis, BBB permeability, microglial activation in the rat model [275]. Despite DFO is an efficient natural chelator, it has a wide range of side effects including renal complications, dysfunction of auditory and visual systems, growth retardation, especially in children [276,277], allergic reactions at the infusion site [278], and neurological side effects at high doses [271]. Some of these side effects are removed by lowering the dose [276,277].…”
Section: Other Iron-chelating Compoundsmentioning
confidence: 99%
“…Despite DFO is an efficient natural chelator, it has a wide range of side effects including renal complications, dysfunction of auditory and visual systems, growth retardation, especially in children [276,277], allergic reactions at the infusion site [278], and neurological side effects at high doses [271]. Some of these side effects are removed by lowering the dose [276,277].…”
Section: Other Iron-chelating Compoundsmentioning
confidence: 99%
See 1 more Smart Citation